Childfree By Choice; Studi Perbandingan Istimbath Dalil Syar’i Pihak Pro dan Kontra - Rauf, Rusmin Abdul (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2023)
This study will compare the arguments used by those who are pro and contra about childfree. Childfree itself means live without children or couples who do not have children. In Indonesia, the issue of Childfree went viral after youtuber Gita Savitri made a statement about her choice to become a married couple without children, the idea of ​​Childfree then became a polemic. Some reject it and some support it. These two different arguments cannot be separated from the use of verses of the Qur’an and the hadith of the Prophet Muhammad SAW. The way these two parties do istimbath on the texts of the Qur'an and the sunnah so that they draw different conclusions is interesting to study. This study found that basically, agreed that as a personal choice, not having children is not forbidden, even though this choice is not in accordance with the advice of the Prophet Muhammad. but if the choice does not have children because it is influenced by the childfree movement, then that right is prohibited.